Strategic assessment of alternative design options for multivoltage-level distribution networks - Gan, Chin Kim; Pudjianto, Danny; Djapic, Predrag; Strbac, Goran (IEEE, 2014)
This paper presents a methodology for assessing the performance of alternative design strategies for multivoltage-level distribution networks. The key feature of the proposed methodology is its ability to reproduce realistic network topologies and lengths, as calibrated against real distribution networks. Through year-round power flow analysis and optimization processes, the proposed approach allows comprehensive network studies to be carried out for the decision makers to investigate the sensitivity to different parameters and to draw more robust conclusions than those reached through a specific network study. The output metrics used for comparison of network performance are overall network cost, network losses, and reliability, which represent the three most crucial network performance indicators in network design. The validity of the developed models was demonstrated through the investigation of alternative distribution network design for a real medium voltage (MV) network in the U.K. This investigation includes quantitative performance evaluation and comparison between a four-voltage-levels design (e.g., 132 kV/33 kV/11 kV or 6.6kV/0.4 kV) with three-voltage-levels network arrangements (e.g.,132 kV/11 kV/0.4 kV or 132 kV/20 kV/0.4 kV) and comparison between the peak demand-driven network design versus the optimal loss inclusive network design.